Global Commerce in Transition: Recent Legal Shifts in International Trade Law - Li, Chengjin (Pacific International Journal, 2024)
This study offers a comprehensive analysis of the evolving landscape of International Trade Law in response to dynamic global forces. Tracing the historical foundations through mercantilism to the contemporary era, the research explores key developments such as the creation of the World Trade Organization, the rise of digitalization, and the integration of environmental and social considerations. Recent legal shifts are examined in terms of the broadening scope, enhanced structure, and augmented complexity of International Trade Law. The study highlights the transformative impact of the COVID-19 pandemic and provides valuable insights for businesses, policymakers, and researchers navigating the complexities of an interconnected and dynamic global economy. As International Trade Law adapts to emerging challenges, the study underscores its pivotal role in fostering fairness, justice, and global economic cooperation.